Media and contemporary tattoo (Communication & Society, 2016)
Tattoo phenomenon, initially associated with traditional ethnic groups and later with marginal cultures, has in recent decades experienced unprecedented expression in contemporary societies spreading out into very diverse segments of the population, where this practice was heretofore alien. Originally associated with rituals and sacred rites, for some, tattoos have become increasingly fashionable, with this trend largely driven by mediated diffusion channels. Accordingly, the presence of tattoos is evident in the street as well as in the media. This paper is an approach to the role of the media in this state of affairs. During the course of this research, in-depth interviews were carried out with professional tattoo artists and individuals who have been tattooed, in order to learn about the various aspects involved in the mediation of the tattoo and in its execution. As a result of these interviews, it has been established that media have influenced the increase in popularity of this practice, both from the clear perspective of the tattoo’s quantitative presence in urban environments, and from the different ways in which visibility has been granted to the tattoo by the media through various platforms and formats involving a variety of areas ranging from, among others, the training of tattoo artists, visual styles, social legitimization of their use, the personal meaning given to tattoos and the reasons for getting tattooed, among others.